Ventral Midbrain NMDA Receptor Blockade: From Enhanced Reward and Dopamine Inactivation - Hernandez, Giovanni; Cossette, Marie-Pierre; Shizgal, Peter; Rompré, Pierre-Paul (Frontiers in Behavioral Neuroscience, 2016)
Glutamate stimulates ventral midbrain N-Methyl-D-Aspartate receptors (NMDAR) to initiate dopamine (DA) burst firing activity, a mode of discharge associated with enhanced DA release and reward. Blockade of ventral midbrain NMDAR, however, enhances brain stimulation reward (BSR), results can be explained by a reduction in the inhibitory drive on DA neurons that is also under the control of glutamate. In this study, we used fast-scan cyclic voltammetry (FSCV) in anesthetized animals to determine whether this enhancement is associated with a change in phasic DA release in the nucleus accumbens. Rats were implanted with a stimulation electrode in the dorsal-raphe (DR) and bilateral cannulae above the ventral midbrain (VM) and trained to self-administer trains of electrical stimulation. The curve-shift method was used to evaluate the effect of a single dose (0.825 nmol/0.5 μl/side) of the NMDAR antagonist, PPPA, on reward. These animals were then anesthetized and DA release was measured during delivery of electrical stimulation before and after VM microinjection of vehicle followed by PPPA. As expected, Phasic DA release and operant responding depended similarly on the frequency of rewarding electrical stimulation. As expected, PPPA produced a significant reward enhancement. Unexpectedly, PPPA produced a decrease in the magnitude of DA transients at all tested frequencies. To test whether this decrease resulted from excessive activation of DA neurons, we injected apomorphine 20 min after PPPA microinjection. At a dose (100 µg s.c.) sufficient to reduce DA firing under control conditions, apomorphine restored electrical stimulation-induced DA transients. These findings show that combined electrical stimulation and VM NMDARs blockade induce DA inactivation, an effect that indirectly demonstrates that VM NMDARs blockade enhances reward by potentiating stimulation-induced excitation in the mesoaccumbens DA pathway.